Logo Hari Kebangsaan 2018: Analisis Teori Seni dan Aplikasi Komunikasi Visual (Malaysian National Day Logo 2018: An Analysis Based on the Theory of Arts and Visual Communication) - Md Yunus, Marzudi; Mohd Nasir, Nuryuhanis; Samsudin, Nurul Haniza (Universiti Kebangsaan Malaysia Press, 2019)
A logo is an important tool for visual communication especially for promotional activity, brand identity and campaigns. It is also an important means to disseminate public information. Additionally, a logo is normally used in creating and representing the corporate image for an event or entity. As a coat of arms for a country, a logo is embedded with deep meaning depicted through various elements on a heraldic visual design. Meanings of a logo can be associated with the local sociocultural context it represents as every design element of a logo has its own significant message or value. This research analyses the logo for the 2018 Independence Day for Malaysia by focusing on the design and the application on the medium it is based on. Every element used in the design is analysed according to art and design elements and principals which includes line, form, colour-tone, space, balance, contrast and pattern. The logo is also analysed based on visual communication theory. This research shows that the structure and design management (which includes colour element and design principles) of the 2018 Independence Day logo is imperfect and has affected the ideal function of a logo as a visual communication tool. Suggestions for futher improvements which will not change the main structure and meaning of the logo design are enclosed in this paper.